Academic well-being amongst university students: the roles of mindfulness and epistemic beliefs on psychological well-being - Ive Emaliana; Alies Poetri Lintangsari; Wahyu Diny Sujannah; Irene Nany Kusumawardani; Al Amirul Eimer bin Ramdzan Ali; Muhammad Afif Alhad (International Journal of Adolescence and Youth)
Grounded in theory that psychological well-being predicts academic well-being, this cross-sectional study surveyed 84 students at Indonesian and Malaysian universities. Validated self-report scales assessed psychological well-being, academic well-being, mindfulness, and epistemic beliefs. Regression revealed psychological well-being explained 55.6 % of variance in academic well-being (β = 0.749, p < .001). Mindfulness correlated moderately with psychological well-being (β = 0.59, p < .001), whereas overall epistemic beliefs were nonsignificant; however, Certain Knowledge and Simple Knowledge showed small yet significant associations (β = 0.21, p = .041). Hayes PROCESS mediation confirmed a strong direct relationship between psychological and academic well-being (β = 0.942, p < .001). Indirect pathways through mindfulness (β = –0.104, 95 % CI [−0.220, 0.013]) or epistemic beliefs (β = 0.000, 95 % CI [−0.022, 0.026]) were minimal. The correlational pattern suggests cultivating present-moment awareness and nuanced views of knowledge may bolster psychological health and, consequently, academic adjustment.